Analysis of Regulatory T Cell Subsets and Their Expression of Helios and PD-1 in Patients with Hashimoto Thyroiditis - Yifang Hu; Lijuan Zhang; Huanhuan Chen; Xiaoyun Liu; Xuqin Zheng; He Shi; Lin Jiang; Dai Cui (International Journal of Endocrinology)
Hashimoto thyroiditis (HT) is an autoimmune disease that presumably arises consequent to loss of immune tolerance to autoantigen in thyroid. Regulatory T cells (Tregs) are considered to play a vital role in maintaining the immune balance, as they own intensive suppressive function. This study was undertaken to analyze numbers of Tregs and their expressions of Helios and PD-1 in HT patients. It also aimed to explore the relationship of these with thyroid function and specific autoantibodies. Peripheral blood mononuclear cells (PBMCs) were extracted from blood of 20 healthy controls (HC) and 42 HT patients with varying thyroid functions (10 overt hypothyroidism, 12 subclinical hypothyroidism, and 20 euthyroidism). We performed flow cytometry analysis in PBMCs to detect CD4+CD25+Foxp3+Tregs and their subsets, including CD45RO+Foxp3high activated Treg cells (aTregs), CD45RO-Foxp3low resting Tregs cells (rTregs), and CD45RO+Foxp3low secreting Treg cells (sTregs), as well as the expression of Helios and PD-1 on these cells. The results showed that the percentage of Tregs, aTregs was significantly lower in HT patients and it showed inverse correlation to thyroid function states, in comparison with these in healthy controls. In addition, patients with HT showed decreased expression of Helios in aTregs, while having increased expression of PD-1 in Tregs and sTregs. The levels of Tregs, aTregs, and Helios expressing aTregs were all negatively correlated with antithyroid antibodies. In conclusion, the deficiency of Tregs frequency and aberrant expressions of Helios and PD-1 may possibly contribute to thyroid immune damage in HT.